Pengukuran Fungsionalitas, Kehandalan, Efisiensi, dan Kegunaan pada Pengembangan Sistem Informasi Pemesanan Tiket Wisata Online pada Lokal Wisata Hutan Pinus Limpakuwus Banyumas - Endang Setyawati; Adhi Wibowo; Diwahana Mutiara Candrasari; Roberto Martins (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2020)
Limpakuwus Village is in the Valley of Mount Slamet. It stretches from the top of the mountain towards the south to the border of Kotayasa Village, Sumbang District. In Limpakuwus village, there are several tourist attractions, one of which is the Limpakuwus Pine Forest. This tour is classified as a new tour, where all ticket sales systems are still not computerized. In making information systems, the author uses a prototype development method. The prototype method is used because it is faster and the user's needs can be precisely identified. The writer collected data for the first time, by directly observing the field, and conducting interviews. Then a prototyping system is made, then directly tested with potential users, namely the manager of the Limpakuwus pine forest. After the data obtained from the distribution of questionnaires, then the researcher wants to measure the prototype of this tour ticket booking information system in terms of usability, reliability, efficiency, and usability. And from the measurement results, it is known that the value of Functionality is 72%, Reliability is 74.3%, Efficiency is 75.6% and Usability is 74.3%.